Cardiac Arrest Following Remimazolam-Induced Anaphylaxis: A Case Report. Issue 9 (23rd September 2022) - Hasushita, Yudai; Nagao, Megumi; Miyazawa, Yoshihide; Yunoki, Kazuma; Mima, Hiroyuki
Abstract : Remimazolam is a recently approved benzodiazepine sedative. We report a case of a 72-year-old man who experienced a cardiac arrest due to severe anaphylaxis immediately after general anesthesia induction. Based on the results of skin tests, including those for dextran 40, an excipient in the remimazolam solution, and a review of drugs given during 3 anesthetics, remimazolam was identified as the probable causative agent. Although remimazolam is structurally similar to midazolam, the patient was not allergic to midazolam as demonstrated before and after anaphylaxis. This report highlights the potential risk of allergic reactions to remimazolam.